Digit ratio (2D:4D), aggression, and testosterone in men exposed to an aggressive video stimulus - Kilduff, Liam P.; Hopp, Renato N. [UNESP]; Cook, Christian J.; Crewther, Blair T.; Manning, John T. (Evolutionary Psychol, 2013)
The relative lengths of the 2nd and 4th digits (2D:4D) is a negative biomarker for prenatal testosterone, and low 2D:4D may be associated with aggression. However, the evidence for a 2D:4D-aggression association is mixed. Here we test the hypothesis that 2D:4D is robustly linked to aggression in challenge situations in which testosterone is increased. Participants were exposed to an aggressive video and a control video. Aggression was measured after each video and salivary free testosterone levels before and after each video. Compared to the control video, the aggressive video was associated with raised aggression responses and a marginally significant increase in testosterone. Left 2D:4D was negatively correlated with aggression after the aggressive video and the strength of the correlation was higher in those participants who showed the greatest increases in testosterone. Left 2D:4D was also negatively correlated to the difference between aggression scores in the aggressive and control conditions. The control video did not influence testosterone concentrations and there were no associations between 2D:4D and aggression. We conclude that 2D:4D moderates the impact of an aggressive stimulus on aggression, such that an increase in testosterone resulting from a challenge is associated with a negative correlation between 2D:4D and aggression.
Keywords: 2D:4D; prenatal testosterone; testosterone; aggressive video